The Role of Legal Deposit of Books in the Polish Library Scheme: The Case of Poznań University Library - Bródka, Małgorzata (Taylor&Francis, 2014)
This article discusses the legal deposit system in Poland, outlining important issues, legal regulations, cooperation with publishers, and the importance of delivering books for academic environment. It emphasizes the significance of legal deposit for shaping collections and improving institutional quality. Poznań University Library is presented as an example of the Polish approach to the issue of book acquisition, including the library's mission statement and elements of its collection development policy. The author also writes about tasks for the Legal Deposit Office and the library in the near future, including implementation of electronic legal deposit in Poland.
Keywords: Poland; legal deposit; obligatory deposit; Polish library law; publishers; collection quality; academic environment; faculty libraries